The influences of Leader-member exchange (LMX) and perceived organizational support toward performance mediated by organizational commitment of Attorney General's Office of the Republic of Indonesia - Lila Agustina; Aryana Satrya (Eduvest - Journal of Universal Studies, 2025)
The performance of the Attorney General's Office of the Republic of Indonesia plays a strategic role in supporting national legal development with professionalism and integrity. One crucial aspect of enhancing the prosecutor's office's performance is strengthening competent and competitive human resources (HR). This study aims to analyze the influence of Leader-Member Exchange (LMX) and Perceived Organizational Support (POS) on the Performance of Attorney General’s Office Personnel, with Organizational Commitment as a mediating variable. This research adopts a quantitative approach, collecting data through surveys conducted among Attorney General’s Office employees. The Leader-Member Exchange (LMX) variable refers to the quality of relationships between leaders and subordinates within the organization, while Perceived Organizational Support (POS) describes the extent to which employees feel supported by the institution. Organizational Commitment, as a mediating variable, explains employee attachment to the organization and its impact on individual performance. The findings of this study are expected to contribute to policy development in HR management at the Attorney General’s Office, particularly in improving personnel professionalism, the effectiveness of training programs, and strengthening workplace relationships between leaders and subordinates. The study’s implications can serve as a foundation for designing strategies to enhance competency, accountability, and legal enforcement efficiency.